Implementation of Smart Environment Policy in Sukoharjo Regency in Supporting Sustainable Development - Muhammad Faiz Abrar Hibatullah; Nunik Nurhayati (Universitas Muhammadiyah Surakarta, 2025)
This research aims to analyze the implementation of Smart Environment in Sukoharjo Regency and Smart Environment policies in Sukoharjo Regency in supporting the principles of sustainable development. This research uses an empirical juridical qualitative approach. This research focuses on the implementation of Smart Environment in Sukoharjo Regency and its relation to the principles of sustainable development, which has not been widely discussed in previous studies. The results showed that the integrated planning of Smart Environment in Sukoharjo Regency consisted of developing the dimensions of the Environmental Protection Program (Protection), developing Waste Management and Responsible Energy Management (Energy). The conclusion of this research is that the implementation of Smart Environment in Sukoharjo Regency has succeeded in achieving sustainable development goals through green open space management, modern and sustainable waste management, independent energy management, and reducing environmental pollution. In addition, the implementation of Smart Environment in Sukoharjo Regency supports sustainable development with the principles of public trust, the precautionary principle, the principle of justice between generations, the principle of subsidiarity, and the polluter pays principle.